Technological Development – A Tool for Social and Economic Impact of the Chamber of Commerce and Industry of Mures County. (2016) - Giurgiu, Anca Mihaela; Manciu, Ionela; Lese, Ioana
Abstract: The purpose of this paper is to present the role of the Chamber of Commerce in implementing new ways of communication within training courses. Thus, some results of the project "Transfer of innovative solutions for VET training of quality professionals" (acronym TIT-us) will be presented, funded by the European Commission, in terms of the involvement of Chamber of Commerce and Industry Mures. It addresses the need to provide a new design for the development of training courses organized by the Chambers of Commerce and also to give them a note of freshness and attractiveness on a market which is in continuing transformation and modernization of teaching methodology.